Next generation plant biostimulants & genome sequencing strategies for sustainable agriculture development - Garg, Shivanshu; Nain, Pooja; Kumar, Ashish; Joshi, Samiksha; Punetha, Himanshu; Sharma, Pradeep Kumar; Siddiqui, Sazada; Alshaharni, Mohammed O.; Algopishi, Uthman Balgith; Mittal, Amit (Frontiers in Microbiology, 2024)
The best environment for plant growth and development is one that contains certain essential metabolites. A broad category of metabolites known as "plant biostimulants" (PB) includes biomolecules like proteins, carbohydrates, lipids, and other secondary metabolites related to groups of terpenes, specific nitrogen-containing compounds, and benzene ring conjugated compounds. Their formation is dependent on both biotic and abiotic factors, like the release of PB by plants, animals, and microorganisms, or it can result from the control of temperature, humidity, and pressure in the atmosphere, as is the case with humic substances (HS). Understanding the genomic outputs of the concerned organism (may be plants or other than them) becomes crucial for identifying the underlying behaviors that lead to the synthesis of these complex compounds. For the purposes of achieving the objectives of sustainable agriculture, detailed research on PBs is essential because they aid in increasing yield and other growth patterns of agro-economic crops. The regulation of homeostasis in plant-soilmicrobe system for survival of humans and other animals is mediated by plant biostimulant action considered essential also for the growth of plants themselves.The genomic size and gene operons for functional & regulation control have so far been revealed through technological implementations, but important gene annotations are still lacking, causing a delay in revealing the information. Nextgeneration sequencing techniques including nanopore, nanoball, and Illumina are essential in troubleshooting the information gaps. These technical advancements have greatly expanded the candidate gene openings. The secondary metabolites being important precursors need to be studied in a much wider scale for accurate calculations of biochemical reactions taking place inside and outside the synthesizing living cell. The present review highlights the sequencing techniques to provide a foundation of opportunity generation for agricultural sustainability.